Fostering entrepreneurial mindsets in underserved communities - a multiple case study of Cape Flats in Western Cape, South Africa - Pastor, Amiena (Graduate School of Business (GSB), 2026)
Entrepreneurship is increasingly viewed as a solution for employment creation and poverty alleviation in developing countries, specifically underserved communities. In developed countries, individuals usually possess both entrepreneurial intentions and competencies and have access to various resources and opportunities to start and scale their businesses. However, those in developing countries do not have access to this. Those who engage in entrepreneurial activities do so for survival and are identified as being part of the informal economy. This study aimed to evaluate a strategy that encourages entrepreneurial mindsets among individuals living in underserved communities on the Cape Flats in the Western Cape by examining three groups and their sustainability methods. To understand the different mindsets regarding entrepreneurship among people living in underserved communities, multiple case studies were conducted with three groups and analysed using thematic analysis. Group 1 was constantly seeking relief from daily life challenges, Group 2 were survivalist entrepreneurs, and Group 3 were opportunity-based or growth-oriented entrepreneurs. The goal was to develop a strategy informed by the experiences, attitudes, practices, and perspectives of individuals in Groups 2 and 3. By understanding their mindsets, we aimed to assist those in Group 1 by providing similar strategies to help them move forward. The research revealed that participants in Group 1 wanted to change their environmental circumstances; however, owing to a lack of entrepreneurial training and resources, they felt trapped and helpless. Some managed to face challenges by starting small businesses, either self-taught or inheriting skills, which mainly consist of artisanal skills. The study suggests that an increase in informal learning in these communities could be a strategy to help lift people out of difficult situations. This approach was explored further by incorporating skill development and entrepreneurial training as constructive interventions facilitated by individuals or groups. These initiatives can help reduce unemployment and address various social issues.